PROBLEMATIKA AKUNTANSI HERITAGE ASSETS: PENGAKUAN, PENILAIAN DAN PENGUNGKAPANNYA DALAM LAPORAN KEUANGAN (Studi Kasus pada Pengelolaan Museum Jawa Tengah Ronggowarsito) - Retha Maya Masitta; Anis Chariri (Diponegoro Journal of Accounting, 2015)
This study aimed to analyze and understand the accounting problems of heritage assets: recognition, valuation and disclosure. Heritage assets is asset that has environment, culture, and nation history value. The advantage of them is not only for ideology importance and academic, but also as economic resource.The observation use case study approach. Data based on the interviews to the managers of Ronggowarsito Museum, related agencies, academics, and antiquities collector; and also the documents analysis found directly on the field. Then, relate them to the available literacy. Based on the research, it is concluded that there is not an appropriate definition to the heritage assets. The informant tends to relate it with Cultural Conservation. Besides the related parties still find some difficulties doing the same economic valuation for all kinds of heritage assets. Procurement of collection is based on the price or value on the Governor Regulation about The Standardization of Activity Cost and Honorarium of Preservation Cost and The Standardization of Supplying Goods/ Sevices Price. But, accountancy practice of heritage assets on managing Ronggowarsito Central Java Museum has appropriate to the accountancy standard as managed by government which stated in CaLK without value.